2012
DOI: 10.1107/s090744491204423x
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure analysis of the relative binding of cisplatin and carboplatin in a mixture with histidine in a protein studied at 100 and 300 K with repeated X-ray irradiation

Abstract: The anticancer agents cisplatin and carboplatin bind to histidine in a protein. This crystal structure study at data-collection temperatures of 100 and 300 K examines their relative binding affinities to a histidine side chain and the effect of a high X-ray radiation dose of up to ∼1.8 MGy on the stability of the subsequent protein-Pt adducts. Cisplatin binding is visible at the histidine residue, but carboplatin binding is not. Five refined X-ray crystal structures are presented: one at 100 K as a reference a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 21 publications
1
13
0
1
Order By: Relevance
“…Might this arise from X-ray absorbed dose effects? In a previous study, 18 we showed that cisplatin binding was stable up to a dose of 1.7 MGy. The total absorbed X-ray doses of each dataset at the three temperatures in this study were 0.31 MGy, 0.37 Mgy, 0.48 MGy, and 0.31 MGy (Table I and Table S1 31 ), and show that the cisplatin and carboplatin should be stable at these absorbed X-ray doses.…”
Section: Discussionmentioning
confidence: 76%
“…Might this arise from X-ray absorbed dose effects? In a previous study, 18 we showed that cisplatin binding was stable up to a dose of 1.7 MGy. The total absorbed X-ray doses of each dataset at the three temperatures in this study were 0.31 MGy, 0.37 Mgy, 0.48 MGy, and 0.31 MGy (Table I and Table S1 31 ), and show that the cisplatin and carboplatin should be stable at these absorbed X-ray doses.…”
Section: Discussionmentioning
confidence: 76%
“…6B), and the mass spectrometry results are shown in Table 1. The histidine content in each identified protein is also included in Table 1, since recent reports suggest that histidine residues in a protein contribute to cisplatin binding [35], [36]. While most of the proteins have low histidine contents, higher levels in casein kinase II and eukaryotic translation initiation factor 3 may contribute to binding of these proteins to cisplatin.…”
Section: Resultsmentioning
confidence: 99%
“…35 However, our structures cannot be directly compared with that obtained for HEWL/carboplatin + cisplatin, 35 since the bis-adduct has not been obtained using the same procedure by Helliwell and Tanley. 35 However, our structures cannot be directly compared with that obtained for HEWL/carboplatin + cisplatin, 35 since the bis-adduct has not been obtained using the same procedure by Helliwell and Tanley.…”
Section: Crystallographymentioning
confidence: 99%